Emerging Role of GPR30/GPER1 in Skeletal Metabolism - J. Ford, Jeffery; Hajibeigi, Asghar; K. Oz, Orhan (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2011)
Estrogens are known to regulate bone growth, mass, and turnover. The actions of estrogens on the skeleton are thought to occur mainly through the action of the nuclear receptors ERα and ERβ. Although, estrogens are commonly thought of as more important in females, estrogen regulation of the male skeleton has been clearly demonstrated in patients with aromatase deficiency or a mutation in the ERα gene or in clinical studies in men using pharmacologic interventions to inhibit estrogen synthesis or estrogen repletion. Recently, in vitro and in vivo studies have shown that the G protein- coupled receptor, GPR30, is a functional estrogen receptor (ER) or modulates tissue response to estradiol. As such it has been renamed GPR30/GPER1. In the absence of any reported human cases of GPR30/GPER1 deficiency, genetically defined mouse models have been used to study the in vivo function of this protein. Female GPR30/GPER1 null mice display reduced body size and bone mass. Ovariectomized females given estradiol replacement display reduced longitudinal skeletal growth, as measured by femur length, and decreased growth plate height in WT but not GPR30KO/GPER1KO mice. In contrast to female mice, male mice with GPR30/GPER1 deficiency have increased body size and bone mass accompanied by increased growth plate proliferation. Additionally, studies of male stromal bone marrow progenitors deficient in GPR30/GPER1 and differentiated in osteogenic medium displayed decreased proliferation and increased mineralized nodule formation. These data demonstrate that GPR30/GPER1 action is an important regulator of skeletal growth and metabolism. The balance between classical ER signaling and GPR30/GPER1 signaling is an important issue to be addressed in order to progress our understanding of bone biology and the treatment of abnormal bone mass and metabolism.
Keywords: osteoprogenitor